2020
DOI: 10.3390/rs12111699
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of Using TechDemoSat-1 and CYGNSS Data to Estimate Soil Moisture over Mainland China

Abstract: Spaceborne Global Navigation Satellite System Reflectometry (GNSS-R) provides a new opportunity for land observation. This study is the first to compare and evaluate the performance of the only two spaceborne GNSS-R satellite missions whose data are publicly available, i.e., the UK’s TechdemoSat-1 (TDS-1) and the US’s Cyclone Global Navigation Satellite System (CYGNSS), for sensitivity analysis with SMAP SM on a daily basis and soil moisture (SM) estimates on a monthly basis over Mainland China. For daily sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…After correcting for the GPS transmitting power, antenna gain, signal travel distance, and wavelength, the derived reflectivity can be representative of the soil water content level and land surface roughness and vegetation conditions. Following [21,22,[24][25][26][27][28][29], the CYGNSS reflectivity is calculated assuming a coherent reflection over land. This reflectivity derived using the coherent reflection assumption has demonstrated a satisfactory performance for estimating surface SM in various previous studies.…”
Section: Cyclone Global Navigation Satellite Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…After correcting for the GPS transmitting power, antenna gain, signal travel distance, and wavelength, the derived reflectivity can be representative of the soil water content level and land surface roughness and vegetation conditions. Following [21,22,[24][25][26][27][28][29], the CYGNSS reflectivity is calculated assuming a coherent reflection over land. This reflectivity derived using the coherent reflection assumption has demonstrated a satisfactory performance for estimating surface SM in various previous studies.…”
Section: Cyclone Global Navigation Satellite Systemmentioning
confidence: 99%
“…To achieve this, CYGNSS uses eight small satellites that orbit the tropics (within ±38 • latitudes). The considerable amount of CYGNSS land observation data also measured in this region has greatly contributed to the development of new SM retrieval approaches from spaceborne GNSS-R [21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The quality of CYGNSS and SMAP data was needed to be evaluated before modeling since the quality of data directly related to the performance of the ML predictions. Hence, the obtained CYGNSS observables calculated for each specular point (SP) acquisition and SMAP data gridded daily over the EASE-grid were first filtered according to the following rules: (1) The CYGNSS reflectivity had to be positive and smaller than 0.1 to remove the anomalies [33]; (2) the incident angle of CYGNSS data was above than 60°are commonly disregarded (a degradation in data quality often occurs at larger incidence angles [39]) [30], [37]; (3) the negative antenna gain in the direction of the specular point (corresponding to uncertainties reported in the measured antenna gain patterns) was removed [28], [34], [35], [37]; (4) to ensure that the error in the CYGNSS SP location estimation is within a reasonable range, only the BRCS data with a Delay Doppler Map (DDM) peak position between the 5th and 11th bins in the delay axis were preserved [35], [40]; (5) the SMAP "retrieval successful/unsuccessful" quality flag was used as well to filter the SMAP data to ensure the quality of SM estimation [31], [41].…”
Section: B Data Quality Controlmentioning
confidence: 99%
“…The previous study [32]- [37] has tried to add alternative ancillary data to improve the accuracy of SM estimates. We found that most of the added ancillary data are related to terrain, such as topography and soil texture [32]- [37].…”
Section: B Sm Estimation Using ML Regression Aided By the Preclassification Strategymentioning
confidence: 99%
See 1 more Smart Citation